A novel fuzzy logic control method for multi-agent systems with actuator faults - Er, Meng Joo (2020)
The leader-following consensus problem for linear multi-agent systems with matched unknown nonlinear and actuator faults under switching topology is addressed in this paper. The main contributions are as follows: (1) In contrast to the existing results under switching topology, the unknown nonlinear considered in this paper are completely unknown; (2) The developed controller is capable of compensating for the actuator faults and the nonlinear simultaneously. To be more specific, by approximating the nonlinear by a fuzzy logical system (FLS) and by introducing switching mechanism in the distributed controller and adaptive update laws, a new FLS-based distributed adaptive controller is developed. By virtue of estimating the norm of weight vector in the FLS, the developed controller can compensate for unknown nonlinear under the actuator faults. In addition, it is proven that the developed controller can guarantee that the consensus errors are uniformly ultimately bounded. An illustrative example demonstrates the effectiveness and efficiency of the proposed method.